IMPLEMENTASI PROGRAM BINA PRIBADI ISLMA DALAM MEMBENTUK KARAKTER PESERTA DIDIK DI SDIT HARAPAN UMMAH KARAWANG - Naina Nurparida; Debidik Nabilatul Fauziah; Neng Ulya (TABYIN: JURNAL PENDIDIKAN ISLAM, 2026)
Islamic Personal Development is an educational and character building activity in the form of group-based studies that are carried out every week. Coaching is not the same as learning because the goal of coaching is the formation of a superior person, not adding knowledge and skills. By combining the national curriculum and the curriculum created by JSIT itself, especially at SD IT Harapan Ummah Karawang which has a special program oriented towards fostering the character of students, namely the "Bina Pribadi Islam" program. This research was conducted using qualitative method descriptive approach. Data collection is done by observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation and data verification. The results of the study concluded that, the implementation of the Islamic personal development program has a schedule during school hours, every Friday which is carried out in the classroom or outside the classroom. There are main activities and supporting activities. In the main activity, students are grouped into several groups, namely 5-12 students. The implementation of activities is separated between the Brotherhood and the akhwat, adjusted again to the material taught. In addition to the main activities, there are also supporting activities. The supporting activities in question are other religious activities that can shape the character of students through habituation and coaching activities that must be taught to students outside of class hours, such as: Mabit, Ifthar jama'I, Tahsin, Tahfizh, Salat congregation, PHBI for application for Islam, PHBN for state insight, Scouting, Market day, Qurban learning, Extracurricular, Journal and literacy. It is sought that all activities in the unit can support the implementation of the Islamic personal development program. There are several supporting and inhibiting factors in the implementation of Islamic personal development programs, including: Supporting factors: Teacher competence, Student activity, School curriculum, Facilities and infrastructure, Parent Support. Inhibiting factors: Teacher attendance, Learning time. The results of the implementation of the Islamic personal development program in the main activity provide students with insight into the understanding of the character building materials provided. While the results of the implementation of the Islamic personal development program at SDIT Harapan Ummah Karawang in supporting activities in shaping the character of students through habituation and coaching activities that must be taught to students outside of class hours, including the following: Mabit, Ifthar jama'I, Tahsin, Tahfizh, Salat congregation, PHBI for application for Islam, PHBN for state insight, Scout Scouting, Qurban learning, Market day, Extracurricular, Journal and literacy. Based on the supporting activities above, character values are implemented from the Islamic personal development program at SDIT Harapan Ummah Karawang, where Islamic personal development activities are the spirit in all school activities.